Entrepreneurship Training About Business Plan Fisheries In Kediri - Fatmawati, Erlin Widya; Astuti, Indah Yuni; Winahyu, Nastiti (Universitas Tunas Pembangunan Surakarta, 2024)
Empowerment is an activity that provides materials and training to participants to make their lives more prosperous. The aim of this empowerment is to provide education to the community regarding businesses in the fisheries sector in urban areas. The method for this empowerment is by delivering material, questions and answers, as well as practice in filling out a draft business plan outline. The result of this empowerment is that participants gain knowledge about the things needed in a business plan, such as research, creating a company profile, determining business goals, preparing supporting documents, explaining business details, making a marketing plan, adapting to the target market, and making a feasibility analysis. business.